2007
DOI: 10.4269/ajtmh.2007.76.896
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis Caused by Leishmania Tropica in Bikaner, India: Parasite Identification and Characterization Using Molecular and Immunologic Tools

Abstract: Identification of new foci of cutaneous leishmaniasis (CL), along with reports of Leishmania donovani causing the disease, is an issue of concern. Clinico-epidemiologic analysis of 98 cases in the endemic regions of Rajasthan state, India, suggested the preponderance of infection in men (62.24%) compared with women (37.75%). Species characterization by internal transcribed spacer 1 (ITS1) polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP), kDNA-PCR, and immunofluorescence assay est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
113
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(124 citation statements)
references
References 29 publications
9
113
2
Order By: Relevance
“…Previous reports confirmed the same results indicating that males are more commonly infected than females, most likely because of their exposure, possibly as a result of occupational contact with the outdoor sand fl y vectors. [18][19][20][21] Moreover, the highest proportion of infection (31.3%) was recorded in 21-30 years age group, and the lowest (10%) was in the 31-40 years age group, which is in agreement with previous reports indicating more exposure as a result of educational and occupational situations. [18][19][20][21] According to the number of lesions in the patients, single lesions were more common (58%) than both double (22%) or multiple lesions (20%), which is consistent with a previous report by Talari et al 7 that showed 69.7% had only one lesion.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous reports confirmed the same results indicating that males are more commonly infected than females, most likely because of their exposure, possibly as a result of occupational contact with the outdoor sand fl y vectors. [18][19][20][21] Moreover, the highest proportion of infection (31.3%) was recorded in 21-30 years age group, and the lowest (10%) was in the 31-40 years age group, which is in agreement with previous reports indicating more exposure as a result of educational and occupational situations. [18][19][20][21] According to the number of lesions in the patients, single lesions were more common (58%) than both double (22%) or multiple lesions (20%), which is consistent with a previous report by Talari et al 7 that showed 69.7% had only one lesion.…”
Section: Discussionsupporting
confidence: 81%
“…This is in agreement with authors' previous report, 18 but not with Kumar et al who indicated that direct microscopy or parasite culture alone detected respectively 65.5% and 48.2% of the positive samples. 20 CL infection was more prevalent among males (63.8%) than females (36.2%). Previous reports confirmed the same results indicating that males are more commonly infected than females, most likely because of their exposure, possibly as a result of occupational contact with the outdoor sand fl y vectors.…”
Section: Discussionmentioning
confidence: 96%
“…Historically, it is known that Leishmania donovani is the aetiological agent for Indian Kala-azar. The species is endemic in the eastern part of the country (Salotra and Singh 2006) whereas L. tropica causing cutaneous disease in India is restricted to the western part (Kumar et al 2007). The causal agent for PKDL is found out to be L. donovani (Salotra et al 2001) and the incidence of PKDL might have importance in the transmission of VL in India, as PKDL provides the only known reservoir of the parasites (Thakur and Kumar 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In recent time, Sharma et al (2005) reported the occurrence of both L. donovani and L. tropica in the Localized Cutaneous Leishmaniasis (LCL) or 'Oriental sore' patients from Himachal Pradesh. LCL is endemic in the deserts of Rajasthan and is known to be caused by L. tropica (Kumar et al 2007). In Sri Lanka, similar type of observation had been Karunaweera et al (2003), where they claimed the cases of Cutaneous Leishmaniasis caused by L. donovani.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical picture of leishmaniasis is heterogeneous and can be classified into three forms: cutaneous (CL), mucocutaneous (MCL), and visceral leishmaniasis (VL). [7] The clinical pattern of the disease showed variation in the severity and duration and low response to treatment in some cases raising the possibility of the existence of different Leishmania species [8] At least 21 species and subspecies of Leishmania have been recorded as being infective to humans, many of which cause extensive morbidity and are responsible for a wide spectrum of clinical symptoms. Cutaneous leishmaniasis is a common skin disease in the Middle East region affecting all ages and both sexes.…”
Section: Introductionmentioning
confidence: 99%